Exploring the Role of Digital Libraries in Primary Schools in the Era of Digitalization: A Systematic Literature Review - Sari, Yunita; Istiqfaroh, Nurul; Sukartiningsih, Wahyu; Mariana, Neni (Journal of Educational Sciences, 2025)
Digital libraries have become an important element in supporting learning in elementary schools along with the rapid development of technology and the digitization of education. This study aims to explore the role of digital libraries in improving the accessibility of learning resources, students' digital literacy, and the effectiveness of teachers' teaching in elementary schools through a Systematic Literature Review (SLR) approach. Data was obtained from 15 reputable journals published in the 2019-2024 time span, with selection using the PRISMA method to ensure the relevance and validity of the studies analyzed. The results showed that digital libraries have a positive impact on the affordability of teaching materials, increase students' interest in reading, and enrich technology-based learning strategies for teachers. In addition, digital libraries play a role in the development of 21st-century skills, such as critical thinking, collaboration, and digital communication. However, the main challenges in the implementation of digital libraries include infrastructure limitations, human resource readiness, and access disparities in certain regions. This study emphasizes the need for strategic policies to optimize digital libraries in primary schools, including improved teacher training and strengthening of technological infrastructure. Thus, digital libraries can function optimally in supporting inclusive and quality learning in the era of digitalization.